STUDI POTENSI BATUAN INDUK HIDROKARBON SATUAN BATULEMPUNG FORMASI RAMBATAN DAERAH WANGON SUB-CEKUNGAN BANYUMAS - Salatun Said (Jurnal Ilmiah Geologi PANGEA, 2020)
ABSTRACT – Identification of rock intervals that may have as a source rock potential is the important first step inhydrocarbon exploration, therefore it is necessary to conduct research on the sedimentary rock containing organicmatter which with a certain level of heat and time can produce hydrocarbons in the form of oil or gas. The objective ofthis study is to identify lithofacies and hydrocarbon source rock potential of Claystone Unit of the Rambatan Formationin the Wangon Area, Banyumas Sub-Basin. Based on outcrop data showed that Rambatan Formation in the study areapredominantly composed of shale with thin intercalation of sandstones. This formation was deposited in the deepmarine environment by turbidity current. Geochemical analysis in order to determine the potential and quality of sourcerock was performed on four samples (BMS-28, KLP-27, KLP-31 and BMS-120) of Rambatan shale. The analysis ofpotential and source rock quality showed TOC content varied from 1.21% - 23.45% indicating “very good” quality.Rock-Eval analisys show that the shale from sample BMS-28 and BMS-120 are poor as hydrocarbon source rock(S2<2.5 kg / ton), while shale from samples KLP-27 and KLP-31 have good potential as hydrocarbon source rock(S2>5 kg / ton). All samples taken from Rambatan shale showed Ro <0.6 indicate hydrocarbon maturation level has notbeen reached. The low values HI of BMS-28 and BMS-120 (HI<100 mg HC / g TOC), reflects that this rock can beclassified as non-source rock, while samples KLP-27 and KLP-31 have HI values of 152 mg HC/g TOC and 294 mgHC/g TOC will tend to produce gas and oil if it reaches maturation level. The values of HI between 100-300 mgHC/gare generally derived from type III and II kerogen which predominantly contain terrestrial and marine organism.Keywords : source rock, potential, quality, and maturity